Penyuluhan Tentang Lesson Study (LS) Untuk Meningkatkan Kompetensi Pedagogik Guru-Guru di SMPN 1 Majene - Ikram, Fadhil Zil; Hijrah, Muh.; Yanti, Reski Wahyu (Sipakaraya : Jurnal Pengabdian Masyarakat, 2023)
Competency development is something that should be done by all professionals, including teachers. There are many competencies that must be mastered by teachers and one of them is pedagogic competence that helps smooth the teaching and learning process. The development of a teacher's competence can be done in a way, either with the help of professionals from other institutions or external parties or by cooperation between teachers within the agency. One form of competency development that teachers can do is lesson study. Counseling on lesson study was carried out at SMPN 1 Majene. The number of participants in this activity were 33 teachers. The purpose of the series of activities carried out is to broaden and increase teachers' insight on one way to develop teacher pedagogic competence, namely by lesson study and assisting teachers in carrying out the initial stages of lesson study preparation. Counseling is also based on observations, interviews, and surveys conducted with the school. The output of the series of activities carried out is that the teacher knows and understands the concept of lesson study and is able to identify problems that occur in class as the first step in preparing for learning in lesson study. The result of the activities that have been carried out is that the teacher understands the concept of lesson study and has been able to carry out the steps of identifying problems in class.